2022
DOI: 10.3390/nu14030524
|View full text |Cite
|
Sign up to set email alerts
|

Care Their Diet and Mind: Association between Eating Habits and Mental Health in Chinese Left-behind Children

Abstract: Studies have shown that the prevalence of mental health problems is high among left-behind children (LBC). Modifiable eating habits may play an important role in promoting mental health among these adolescents. This study aimed to investigate the situation of dietary habits and their association with mental health problems in a sample of Chinese LBC. We conducted this cross-sectional study in an economically disadvantaged area of China in May 2020. Information on socio-demographic factors, eating habits (the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, in rural China, many parents might have left their hometowns to work in distant places, resulting in more than 61 million children being left behind [78]. Rural adolescents lacking close parental supervision and protection were more vulnerable to bullying victimization due in part to their lack of self-esteem, sense of security, or unhealthy lifestyles [66,[79][80][81]. Furthermore, the current study indicated that rural adolescents living in a nuclear family and not boarding at school experienced a higher risk of poly-bullying victimization than their urban counterparts, which to some extent was not surprising because poly-bullying victimization was associated with paternal problematic behaviors such as excessive alcohol consumption [82].…”
Section: Discussionmentioning
confidence: 99%
“…However, in rural China, many parents might have left their hometowns to work in distant places, resulting in more than 61 million children being left behind [78]. Rural adolescents lacking close parental supervision and protection were more vulnerable to bullying victimization due in part to their lack of self-esteem, sense of security, or unhealthy lifestyles [66,[79][80][81]. Furthermore, the current study indicated that rural adolescents living in a nuclear family and not boarding at school experienced a higher risk of poly-bullying victimization than their urban counterparts, which to some extent was not surprising because poly-bullying victimization was associated with paternal problematic behaviors such as excessive alcohol consumption [82].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the weighted prevalence of anemia and stunting among LBC was 26.5% and 16.6%, respectively, and emphasized the household food insecurity associated with both conditions [9]. Furthermore, studies have shown that LBC are more likely to have poor lifestyles, including internet addiction [10], smoking [11], excessive drinking [12], and skipping breakfast [13], compared with non-left-behind-children (NLBC). LBC are also at risk of suffering from various psychological problems [14][15][16],…”
Section: Introductionmentioning
confidence: 99%
“…One study focused on preschoolers in rural China suggested that dietary diversity was related to improving children's mental health ( 6 ). Liang et al centered on left-behind children and found that lower frequencies of eating breakfast and fruits were significant factors associated with higher risks of mental health problems ( 23 ). Epidemiological evidence based on large populations and centered around specific food categories is desiderated.…”
Section: Introductionmentioning
confidence: 99%